Effect of gypsum and zinc on soil properties under sodic irrigation in south western Haryana - Kumar, Kapil; Rajpaul; Rathee, Deepika; Ram Prakash; Kavita; Kumar, Pankaj; Ashish (Journal of Soil Salinity and Water Quality, 2023)
An experiment was conducted under field conditions during rabi2021-22 at farmer field in Mahendergarh District, to study the effect of gypsum and zinc on soil properties under sodic irrigation. The experiment was laid out in a randomized block design with three replications and treatments comprised four levels of gypsum (G0, G50, G75 and G100) and four levels of zinc (0, 5, 10 and 25 kg Zn ha-1). The mean soil pHs (9.11) in control is significantly decreased with increase in gypsum levels up to G100 (8.56) whereas zinc application did not significantly influence the soil pH. Significantly higher soil EC1:2 (0.88 dS m-1) was recorded under G100 treatment. While the lowest soil EC (0.43) was recorded under control (G0). Significantly higher organic carbon (0.39%) was observed in G100 treatment over the G0 (0.31%). Exchange sodium percent (ESP) is significantly decreased with the increase in gypsum level. Significantly decrease in ESP (33.0%) was recorded under G100 treatment over control G0 (43.3). Whereas zinc application did not significantly influence the soil pH and EC, organic carbon and ESP. The available N,P,K,Zn and Ca in soil is significantly increased with the application of gypsum and zinc over control. The interactive effect of gypsum and zinc in this present investigation was found non-significant.